2023
DOI: 10.3390/molecules28073075
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Volatile Profiles of Insect Flours by (HS)-SPME/GC-MS: A Preliminary Study

Abstract: The growing world population, combined with scarcities of agricultural land, water, forest, fisheries, and biodiversity resources, makes it necessary to search for alternative sources of nutrients. For this reason, in recent years, edible insects have been introduced into the diet, even in areas where entomophagy is not traditional. In light of this, the present study aims at characterizing the aromatic profile of three edible insects flours: cricket (Acheta domesticus, CP), buffalo worm (Alphitobius diaperinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Cricket volatile compounds are among the factors affecting flavor; for instance, they are responsible for cricket-related odor [ 24 ]. In previous research, approximately 40–60 volatile compounds have been identified in edible cricket powder, 14 of which have also been determined as being related to cricket-related odor [ 24 , 25 , 26 ]. In this study, we identified approximately 50 volatile compounds in both cricket powders ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cricket volatile compounds are among the factors affecting flavor; for instance, they are responsible for cricket-related odor [ 24 ]. In previous research, approximately 40–60 volatile compounds have been identified in edible cricket powder, 14 of which have also been determined as being related to cricket-related odor [ 24 , 25 , 26 ]. In this study, we identified approximately 50 volatile compounds in both cricket powders ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%